Changes in epidemiology and care strategies at the Norwegian National Burn Centre over 35 years (1986-2020) - Henning Onarheim; Ragnvald Ljones Brekke; Fatemeh Zamanzad Ghavidel; Anne Berit Guttormsen; Stian Kreken Almeland (Elsevier, 2023)
Introduction: We evaluated trends in admissions, % TBSA (total body surface area) burnt, age, and outcomes over a 35-year period at the national burn centre in Norway. Methods: Relevant data were extracted from the departmental quality registry covering all acute admissions for burns during 1986-2020. Results: In 1986-2020 there were 2.889 admissions for burns (67.6 % males), with a 110 % increase in 2016-20 when compared to 1986-90. Admissions of children <2 years increased by 400 %. In 2011-20, 66.5 % of patients were transferred from other hospitals.The median area injured declined markedly, from 16.5% TBSA in 1986-90 to 4.5% TBSA in 2016-20.Changes in care included an increased focus on non-delayed referrals and transfers, an explicit intent to achieve early excision within 48 h, and a transition from a highly frequent to a less frequent dressing changes scheme.Mortality declined from 10.9 % to 3.0 %. In 2011-20 the mortality among actively treated patients was 2.4 %. For patients with Baux scores 80-119, mortality declined from 36.0 % (1991-2010) to 18.2 % (2011-20) (P < 0.001). Discussion: Since 1986, more patients have been referred to the burn centre, many of younger ages and with more minor burns. Survival of patients with Baux scores 80-119 increased significantly.